Dehazing Based on Long-Range Dependence of Foggy Images - Yuan, Hong Xu; Liao, Zhiwu; Wang, Rui Xin; Dong, Xinceng; Liu, Tao; Long, Wu Dan; Wei, Qing Jin; Xu, Ya Jie; Yu, Yong; Chen, Peng; Hou, Rong (Frontiers in Physics, 2022)
Deep neural networks (DNN) with long range dependence (LRD) have attracted more and more attention recently. However, LRD of DNNs is proposed from the view on gradient disappearance in training, which lack of theory analysis. In order to prove LRD of foggy images, the Hurst parameters of over 1000 foggy images in SOTS are computed and discussed. Then, Residual Dense Block Group (RDBG) which has additional long skips among two Residual Dense Blocks (RDB) to fit LRD of foggy images, is proposed. RDBG can significantly improve the details of dehazing image in dense fog and reduce the artifacts of dehazing image.